Atlantic water properties, transport and heat loss from mooring observations north of Svalbard - Koenig, Zoe Charlotte; Kalhagen, Kjersti; Kolås, Eivind Hugaas; Fer, Ilker; Nilsen, Frank; Cottier, Finlo (Journal of Geophysical Research: Oceans, 2022)
The Atlantic Water inflow to the Arctic Ocean is transformed and modified in the area north of Svalbard, which influences the Arctic Ocean heat and salt budget. Year-round observations are relatively sparse in this region partially covered by sea ice. We took advantage of one-year-long records of ocean currents and hydrography from seven moorings north of Svalbard. The moorings are organized in two arrays separated by 94 km along the path of the Atlantic Water inflow to investigate the properties, transport and heat loss of the Atlantic Water in 2018/2019. The Atlantic Water volume transport varies from 0.5 Sv (1 Sv = 10 6 m 3 s −1 ) in spring to 2 Sv in fall. The first mode of variation of the Atlantic Water inflow temperature is a warm/cold mode with a seasonal cycle. The second mode corresponds to a shorter time scale (6–7 days) variability in the onshore/offshore displacement of the temperature core linked to the mesoscale variability. Heat loss from the Atlantic Water in this region is estimated, for the first time using two mooring arrays and conserving the volume transport. The heat loss varies between 302 W m −2 in winter to 60 W m −2 in spring. The onshore moorings show a westward countercurrent driven by Ekman setup in spring, carrying transformed-Atlantic Water. The offshore moorings show a bottom-intensified current that covaries with the wind stress curl. These two mooring arrays allowed for a better comprehension of the structure and transformation of the slope currents north of Svalbard.